2017
DOI: 10.26719/2017.23.8.543
|View full text |Cite
|
Sign up to set email alerts
|

Modifying attitude and intention toward regular physical activity using protection motivation theory: a randomized controlled trial

Abstract: Modification de l'attitude et de l'intention vis-à-vis d'une activité physique régulière à l'aide de la théorie de la motivation à la protection : essai contrôlé randomisé RÉSUMÉ Nous nous sommes servis de la théorie à la motivation à la protection pour tester l'impact des entretiens motivationnels sur l'attitude et l'intention des femmes obèses et en surcharge pondérale vis-à-vis de la pratique d'une activité physique régulière. Lors d'un essai contrôlé randomisé, 60 femmes obèses et en surcharge pondérale se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Perceived behavioral control indicates that one's perceived self-efficacy represents one's belief in being able to act. Perceived behavioral control was the most critical variable for predicting high school students' fast food consumption [ 43 ], choosing fruits and vegetables for South Asians [ 44 ], and predicting the intention to avoid food with additives [ 45 ]. Numerous studies have found that attitude, subjective norm, and perceived behavioral control affect consumer behavioral intention.…”
Section: Introductionmentioning
confidence: 99%
“…Perceived behavioral control indicates that one's perceived self-efficacy represents one's belief in being able to act. Perceived behavioral control was the most critical variable for predicting high school students' fast food consumption [ 43 ], choosing fruits and vegetables for South Asians [ 44 ], and predicting the intention to avoid food with additives [ 45 ]. Numerous studies have found that attitude, subjective norm, and perceived behavioral control affect consumer behavioral intention.…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with the result of several studies which suggest that people associate the coping mechanisms highly effective than threat mechanism for maintaining exercise with combating obesity. 12,13,17 Educational intervention and health literacy towards obesity This study shows that mean score of health literacy towards obesity and physical activity was increased after the intervention where mean score 5.48±5, 18.08±2.56 before and after intervention respectively. There was significant difference on health literacy before and after the intervention that means health literacy play important role to increase physical activity intention.…”
Section: Educational Intervention and Severity Towards Obesitymentioning
confidence: 63%
“…Similar study conducted in Iran revealed that intervention package increased weight loss and severity scores. 12,15 Educational intervention and self-efficacy towards physical activity Present study showed that the mean score on self-efficacy is marginally significant (p=0.049). This result is consistent with the result of several studies which suggest that people associate the coping mechanisms highly effective than threat mechanism for maintaining exercise with combating obesity.…”
Section: Educational Intervention and Severity Towards Obesitymentioning
confidence: 63%
See 1 more Smart Citation
“…A study by [21], examine the initial effectiveness of motivational assessments and cognitive behavioral therapies for long-term physical activity in adults with chronic conditions of health using motivational interviewing (MI). Information on age, gender, employment statues and health conditions was collected.…”
Section: Motivational Interviewingmentioning
confidence: 99%